On the tool use behavior of the bonobo‐chimpanzee last common ancestor, and the origins of hominine stone tool use. Issue 10 (7th April 2014) - Haslam, Michael
<x xml:space="preserve">Abstract</x> The last common ancestor (LCA) shared by chimpanzees (Pan troglodytes) and bonobos (P. paniscus) was an Early Pleistocene African ape, which, based on the behavior of modern chimpanzees, may be assumed to be a tool‐using animal. However, the character of tool use in the Pan lineage prior to the 20th century is largely unknown. Here, I use available data on wild bonobo tool use and emerging molecular estimates of demography during Pan evolution to hypothesise the plausible tool use behavior of the bonobo‐chimpanzee LCA (or "Pancestor") at the start of the Pleistocene, over 2 million years ago. This method indicates that the common ancestor of living Pan apes likely used plant tools for probing, sponging, and display, but it did not use stone tools. Instead, stone tool use appears to have been independently invented by Western African chimpanzees (P. t. verus) during the Middle Pleistocene in the region of modern Liberia‐Ivory Coast‐Guinea, possibly as recently as 200, 000–150, 000 years ago. If this is the case, then the LCA of humans and chimpanzees likely also did not use stone tools, and this trait probably first emerged among hominins in Pliocene East Africa. This review also suggests that the consistently higher population sizes of Central African chimpanzees (P. t. troglodytes) over the past million years may have contributed to the increased complexity of wild tool use seen in this sub‐species today. Am. J. Primatol. 76:910–918, 2014. © 2014 Wiley Periodicals, Inc.